Model Pelaksanaan Inisiasi Menyusu Dini (IMD) Pada Ibu Bersalin Di RSUD Prof. Dr. Soekandar Mojosari Mojokerto - Hety, Dyah Siwi (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2014)
In this study aims to analyze the implementation of Early Initiation of Breastfeeding, analyze implementation constraints and develop models of the implementation of Early Initiation of Breastfeeding on maternal. This research uses a qualitative study, future research on starting December 2012 until July 2013.Informan research midwives and maternal. The research method uses observation, in-depth interviews and focus group disscusion. Researchers own research instrument, checklist, interview guide and focus group guide disscusion. Descriptive analysis of the description, which includes the step of data collection, reduction and presentation of data. The results of observations on the direct maternal midwife directly by the command to hold her baby. Barriers that happens is tiredness and hunger. Results of in-depth interviews saying only pregnant women information about nutrition, information about the initiation of early breastfeeding mother knows only partially. Focus Group Results disscusion maternal expect information about early breastfeeding initiation given time pregnancy check and families may wait time of delivery. The observation of the midwife, seem hasty and not in accordance with the Standard Operational Procedure is in the hospital. Results of in-depth interviews, all midwives could explain the steps to implement correctly. Barriers that happens is, a shortage of midwives. Focus Group Results disscusion all midwives said to be realized additional midwives. Early Initiation of Breastfeeding Early implementation is not in accordance with the Standard Operational Procedure. Bottleneck that occurs in the maternal fatigue, hunger and ignorance about Early Initiation of Breastfeeding mom. Barriers on the midwife, a shortage of midwives so that the implementation of Early Initiation of Breastfeeding was not optimal. Model development by involving husbands or families. Socialize hospital guidelines contained in the Standard Operational Procedure and facilities have used standard. Supervision and reminded all midwives to record activities Early Initiation of Breastfeeding.Keywords: models, early initiation of breastfeeding, maternal.Â Â Â